2007
DOI: 10.1243/14750902jeme77
|View full text |Cite
|
Sign up to set email alerts
|

Soft and hard computing approaches for real-time prediction of currents in a tide-dominated coastal area

Abstract: The prediction of tidal currents in the coastal region on a real-time or online basis is useful in taking operation-and planning-related decisions such as towing of vessels and monitoring of oil slick movements. Currently, however, this is done in offline mode on the basis of the statistical method of harmonic analysis involving fitting of harmonic functions to measured data. Alternatively, numerical solutions of hydrodynamic models can also provide spatial and temporal information on currents. Owing to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In another earlier works of GP current predictions over a time step of twenty minutes, one hour, 3 hours, 6 hours, 12 hours and 24 hours at 2 locations in the tidal dominated area of the Gulf of Khambhat along west coast of India was carried out using two soft techniques of ANN and GP and 2 hard techniques of traditional harmonic analysis and ARIMA [16]. The work involved antecedent values of current only to forecast the current for various lead times at these locations.…”
Section: Applications In Ocean Engineeringmentioning
confidence: 99%
“…In another earlier works of GP current predictions over a time step of twenty minutes, one hour, 3 hours, 6 hours, 12 hours and 24 hours at 2 locations in the tidal dominated area of the Gulf of Khambhat along west coast of India was carried out using two soft techniques of ANN and GP and 2 hard techniques of traditional harmonic analysis and ARIMA [16]. The work involved antecedent values of current only to forecast the current for various lead times at these locations.…”
Section: Applications In Ocean Engineeringmentioning
confidence: 99%
“…Several types of ANN are found to be more accurate in comparison with these methods. Recently, researchers [5], [6], [7], [8] found GP to be a promising tool to estimation oceanic parameters.…”
Section: Gp In Ocean Engineegringmentioning
confidence: 99%
“…Alternatively an ANN can be trained using locationspecific measurements and used for forecasting, (as done in Charhate et al 2007) such an approach based entirely on data-driven schemes has not received wide acceptance from the user community who traditionally believes in the physics-based approach. We have therefore tried to combine both numerical as well as data driven techniques in this work.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of ANN applications in ocean engineering in general has been given in (Jain and Deo 2006). In particular Charhate et al (2007) have shown how ANN's can effectively carry out short term current forecasting in a tide dominated bay based on real time current measurements made at a specific site. Similarly Saha et al (2015) have demonstrated how efficiently trained networks can overcome certain deficiencies of such ANN methods.…”
Section: Introductionmentioning
confidence: 99%